Newton's method for solving optimal shape design problems - Magreñán, Á. Alberto; Argyros, Ioannis K (Contemporary study of iterative methods: convergence, dynamics and applications, 2021)
In this chapter we present some results related to Newton's method in order to extend the solvability of optimal shape design problems. Moreover, some numerical examples are also presented in the chapter.
Capítulo del libro "Contemporary study of iterative methods: convergence, dynamics and applications"
Keywords: optimal shape design problems; Newton's method; semilocal convergence; WOS(2)